Islamic Zero Point in the Archipelago: Traces of Islamic History in Barus City, Central Tapanuli - khairunnisa (EDUCATE : Journal of Education and Culture, 2023)
Barus is an area located in Central Tapanuli Regency, North Sumatra Province. Barus has been inaugurated by the President of the Republic of Indonesia, Mr. Ir. Joko Widodo as the first place for the spread of Islam in Indonesia. The President of the Republic of Indonesia also signed the inauguration of the Zero Point Monument of Islam Nusantara in Barus. This determination was based on studies by researchers, public requests, and various historical literature which indicated that Barus was the location where Islam first descended in Indonesia. This can also be seen by the presence of Islamic relics in Barus. One of the remains of the Mahligai tomb site and the Papan Tinggi tomb site which spread Islam is estimated to be in the 5th century AD. However, establishing Barus as the initial location of Islam in the archipelago has raised debate from historians and certain communities. So far, the public considers that Aceh is the location of Islam for the first time in Indonesia. The debate about the entry of Islam has made the author need to dig deeper into the traces of Islamic history in the city of  Barus.